INTENSITY TRANSFORMATION FOR THE MIXTURE COMPOSITIONS OF THE SOLID LUBRICATING BY LACTIN OF LARGE GRAIN LABA AT 1% EFFECT OF METHACRYLIC ACID - G.A. Yeroshenko; Yu. V. Timoshenko (Український стоматологічний альманах, 2019)
An increase in the average life expectancy of a person, the occurrence of pathology of solid teeth tissues, periodontal tissues, leads to progressive loss of teeth. In connection with this, there is a need for dentures. However, many patients (30%) of the prosthesis can not use them, or use them only when eating and speaking.